INDUKSI KALUS EKSPLAN DAUN DURIAN (Durio zibethinus Murr. cv. Selat Jambi) PADA BEBERAPA KOMBINASI 2,4-D DAN BAP (Callus Induction Explants Leaf Durian (Durio zibethinus Murr. cv. Selat Jambi) With 2,4-D And Bap Combination) - . Lizawati; . Neliyati; Retna Desfira (Bioplantae, 2012)
The aim of this study was to obtain the best combination of 2,4-D and BAP in inducing callus from leaf explants durian cv. Selat Jambi. Experiment was arranged in completely randomized design with a growth regulators combination of treatment 2,4-D (1, 2, 3, 4, 5, 6, 7 ppm) and BAP (0,0 ; 0.5 ppm). Each treatment consisted of 10 bottles each culture bottle were planted on explant culture. Explants were cultured on induction medium for 2 month. The parameter time of calli initiation were observed every day. Meanwhile the percentage of explant forming callus, callus structure and color of callus was observed at the end of the study. The results showed that, granting some combination of growth regulators 2,4-D and BAP are given to the culture medium was able to stimulate the formation of callus on leaf explants young durian CV. Selat Jambi. Time of the fastest callus initiation (8 days after cultur) was obtained on medium 4 ppm 2,4-D + 0.5 ppm BAP. In contrast, the highest percentage of explants forming callus was obtained on treatment of 5 ppm 2,4-D (30%).Key words: Exsplants, Durio zibethinus, callus, BAP, 2,4-D